Systematic assessment of microRNAs associated with lung cancer and physical exercise - Liu, Yang; He, Libo; Wang, Wang (Frontiers in Oncology, 2022)
It has long been evident that physical exercise reduces the risk of cancer and improves treatment efficacy in tumor patients, particularly in lung cancer (LC). Several molecular mechanisms have been reported, but the mechanisms related to microRNAs (miRNAs) are not well understood. MiRNAs modulated various basic biological processes by negatively regulating gene expression and can be transmitted between cells as signaling molecules. Recent studies have shown that miRNAs are actively released into the circulation during exercise, and are deeply involved in cancer pathology. Hence, the role of exercise intervention in LC treatment may be further understood by identifying miRNAs associated with LC and physical activity. Here, miRNAs expression datasets related to LC and exercise were collected to screen altered miRNAs. Further bioinformatic approaches were performed to analyze the value of the selected miRNAs. The results identified 42 marker miRNAs in LC, of which three core-miRNAs (has-miR-195, has-miR-26b, and has-miR-126) were co-regulated by exercise and cancer, mainly involved in cell cycle and immunity. Our study supports the idea that using exercise intervention as adjuvant therapy for LC patients. These core-miRNAs, which are down-regulated in cancer but elevated by exercise, may act as suppressors in LC and serve as non-invasive biomarkers for cancer prevention.